ANALISIS PERILAKU ANAK USIA DINI (STUDI PADA PENGGUNAAN APLIKASI TIK-TOK PADA ANAK USIA DINI DI KECAMATAN KAMPA KABUPATEN KAMPAR) - Sutia Nurhidayati; Hukmi Hukmi; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: the purpose of this study was to analyze the behavior of early childhood (study on the use of the tiktok application in early childhood in Kampa sub- District, Kampar District. This type of research is used descriptively which tries to describe the behavior of early childhood caused by the use of the tiktok application. This research was conducted with quantitative and qualitative approaches, whit measuring tools in the form of questionnaires and interviews. The total population used in this study was 275 childre from 12 kindergartens in Kampa District sub-District, Kampar District, then interviewa and observations were made with teachers and school principals, along with their parents, so that the number of children who used the tiktok application along with their parents was obtained, as many as 56 students who were conducted by purposive sample. The data analiysis technique used in the first qualitative data analysis, namely by data reduction, data presentation, drawing conclusions. The second data collection technique is quantitative data analysis, namely by calculating the percentage with the percentage criteria between 76%-100% being said to be very high, the percentage between 56%-75% is said to be high, the percentage between 40%-55% is said to be moderate, the percentage is less than 40% is said to be low.Key Words: Early Childhood Behavior, Tiktok Application